2014
DOI: 10.1093/hmg/ddu399
|View full text |Cite
|
Sign up to set email alerts
|

Rare mutations associating with serum creatinine and chronic kidney disease

Abstract: Chronic kidney disease (CKD) is a complex disorder with a strong genetic component. A number of common sequence variants have been found to associate with serum creatinine (SCr), estimated glomerular filtration rate (eGFR) and/or CKD. We imputed 24 million single-nucleotide polymorphisms and insertions/deletions identified by whole-genome sequencing of 2230 Icelanders into 81 656 chip-typed individuals and 112 630 relatives of genotyped individuals over the age of 18 with SCr measurements. The large set of seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 47 publications
1
57
0
Order By: Relevance
“…It has been shown that variants poorly tagged by GWAS arrays and HapMap imputation, particularly low-frequency variants (1% ≤ MAF ≤ 5%), can explain additional variability13. Recent technological advances resulted in large collections of whole-genome sequence data, such as those from The 1000 Genomes project1415.…”
mentioning
confidence: 99%
“…It has been shown that variants poorly tagged by GWAS arrays and HapMap imputation, particularly low-frequency variants (1% ≤ MAF ≤ 5%), can explain additional variability13. Recent technological advances resulted in large collections of whole-genome sequence data, such as those from The 1000 Genomes project1415.…”
mentioning
confidence: 99%
“…For association testing in the case–control analysis, we used logistic regression; disease status was treated as the response and genotype counts were used as covariates. We also included in the model as nuisance variables the following available individual characteristics that correlate with disease status; county of birth, sex, current age or age of death (first- and second-order terms included), availability of blood sample for the individual and an indicator function for the overlap of the timespan of phenotype collection with lifetime of the individual114445. We applied LD score regression to estimate a correction factor to distinguish polygenicity from population stratification in the GWAS results46.…”
Section: Methodsmentioning
confidence: 99%
“…It is also worth noting that although SLC22A6 and SLC22A8 are categorized as OATs, they are closely related to SLC22A1 (also known as OCT1) and SLC22A2 (OCT2) — which are members of the OCT subfamily of SLC22 transporters — and can transport some organic cations 51 . This may be physiologically important for molecules such as creatinine, which is widely used in the clinic as a marker of renal function 69 and is transported by OCTs, MATEs and OATs 6973 .…”
Section: Slc and Abc Drug Transportersmentioning
confidence: 99%